The effect of intermittent cold exposure on the level of reactive oxygen species production in erythrocytes of rats with induced polycystic ovary syndrome - Hromko, Yevheniia; Zhulikova, Maryna; Myroshnychenko, Mykhailo; Nakonechna, Oksana (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):243